(untitled) (Archaeologia Adriatica, 2009)
The article deals with two unique finds of Eeneolithic acephalic idols unearthed in the course of excavations in 2010 at the Buković − Lastvine site in Benkovac near Zadar. The idols have been only partly preserved. They were found close to each other in a very shallow pit on the very inner edge of a larger pit structure, but outside of any ritual context. They belong to a safe stratigraphic context composed of channelled pottery characteristic of the early Eneolithic in the eastern Adriatic.